Analysis of access to higher education for people with disabilities in institutions of Higher Education and Education for Work and Human Development in the Department of Atlántico - Mercado Ospino, Andrea; de la Cruz Almanza, Sadan; Morales González, Kenkin (Corporación Universitaria Americana, 2023)
This article analyzes through a pilot study, the characteristics of access to higher education for Persons with Disabilities (PWD) in the Departamento del Atla?ntico. The analysis was made based on information collected through surveys of higher education institutions (HEIs), and institutions of Education for Work and Human Development (ETDH) recognized by Ministerio de Educacio?n Nacional with whom inquired about the institutional policies for inclusion, incentives, and strategies designed to promote higher education of this population group. The results indicate the leadership of two HEIs in terms of inclusion, but outside these, the need for clear strategies, processes adapted to the needs of this population, and incentives or economic support focused on the access and permanence of this population both in the IES as in the institutions of ETDH.